Pengaruh Dana Pihak Ketiga dan Tingkat Suku Bunga Kredit Terhadap Profitabilitas di PT. Bank Pembangunan Daerah Bali Tahun 2011-2018 - I Gusti Putu Khresna Kusumawardhana; I Made Sara; Anak Agung Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2021)
The banking have important role in development and a country’s economy. The bank has a task for raise funds from the public in shape saving, deposit, current account and channeling it back to the public in shape credit. In process credit channeling the bank hope get the maximum profit, because with increasing profitability bank activities can work smoothly and optimally. This research aims to test the impact third-party funds and credit interest rate against profitability (Return On Assets) at PT. Bali Regional Development Bank on quarterly I. 2011 to quarterly IV. 2018 using multiple linear analysis methods. The results show that the t-test on variable third-party funds has negative and not significantly effect to profitability (Return On Asset) and credit interest rate has negative and significantly effect to profitability (Return On Assets). While the results F-test obtained variable third-party funds and credit interest rate has positive and significantly effect to profitability (Return On Assets) at PT. Bali Regional Development Bank.